Postoperative coronary artery spasm after mitral valve replacement() - Pragliola, Claudio (Int J Surg Case Rep, 2015)
INTRODUCTION: Postoperative coronary artery spasm is an infrequent life-threatening event after cardiac surgery which can occur without an underlying coronary disease PRESENTATION OF CASE: We report a documented case of a 67-year-old man with normal coronary arteries submitted to mitral valve replacement. Immediately after surgery he had a ST elevation in the inferior leads, and an inferior wall hypokinesia at the trans-oesophageal echo. A coronary angiography demonstrated a focal spasm in the right coronary artery which was successfully treated by intracoronary injection of nitrates. The following postoperative course was uneventful and the left ventricular function returned to normal. DISCUSSION: A coronary artery spasm should be suspected whenever a postoperative infarction occurs after valvular surgery especially in absence of associated coronary artery disease. In this cases postoperative coronary angiography allows both the diagnosis and the treatment. CONCLUSION: This case-report summarizes the findings of this rare and potentially life-threatening cause of early postoperative ischemia and highlights the role of early coronary angiography in the cases of suspected myocardial infarction after cardiac surgery